“Reversed” New Historicism and the Latvian Literature: Gundega Repše’s Novels - Jansone, Ilze (Colloquia, 2025)
The article1 offers an interpretation of Latvian writer Gundega Repše’s novels within their historical context by exploring interpretative possibilities of New Historicism. As a literary theory, New Historicism is an open and opaque methodology, inviting a playful engagement with methods, agencies, and interpretative strategies, and encouraging critical thinking within a theoretical discourse. I also propose that Repše’s novels might be read as a literary practice of what might be called “reversed” New Historicism by which I mean a particular method of creative writing that reinforces the correlation between history and literature and rhizomatic thinking. It helps to reveal systems and assumptions of power and comment on them from below, this way shaping new ways of how we think of fiction, history and language. In my interpretation, I demonstrate that “reversed” New Historicism as a method of creative writing encourages to rethink the continuous presence of power structure that still exists in contemporary society. A network of memories, displayed through artistic language, helps to see the present-day situation and the continuity of the past more clearly.
Keywords: new historicism; creative writing; rhizome-like narrative; Gundega Repšė